2016
DOI: 10.1093/jee/tow055
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance, Host Suitability, and Feeding Injury of the Brown Marmorated Stink Bug,Halyomorpha halys(Heteroptera: Penatomidae), in Selected Vegetables

Abstract: The invasive brown marmorated stink bug,Halyomorpha halys(Stål) (Heteroptera: Penatomidae), is a major pest of agricultural crops in the Mid-Atlantic States. Here we report the seasonal abundance, host preference, and injury potential ofH. halyson tomato, bell pepper, green bean, sweet corn, eggplant, and okra in a small-scale, diversified vegetable farm setting. Life-stage densities, feeding injury, and crop phenology were monitored throughout the growing season in each crop. Populations consisted of both ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…The clear dominance and high abundance of BMSB nymphs (and exuviae) present and the severe feeding damage recorded in the two crops confirm the results of previous studies (e.g. 25, 29,31,32) that bean and pepper are major hosts of BMSB.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The clear dominance and high abundance of BMSB nymphs (and exuviae) present and the severe feeding damage recorded in the two crops confirm the results of previous studies (e.g. 25, 29,31,32) that bean and pepper are major hosts of BMSB.…”
Section: Discussionsupporting
confidence: 88%
“…28,29,30,31,32,33). Beans (in particular Phaseolus vulgaris L.) and peppers (Capsicum annuum L.), the plants being in the focus of our survey, have been shown to be attractive hosts of the stink bug species (23,25,29,30,31,32,33). Symptoms of damage differ according to the plant species affected, and these have been described and illustrated by Kuhar et al (29) and Rice et al (25).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…An electivity analysis identified that BMSB is more commonly found on non-Asian host plants than on Asian host plants in the United States (90). Regardless of host plant, BMSB females oviposit more frequently on crops with long fruiting periods, including some fruiting vegetables (163). BMSB also feeds on small fruit and grapes (131,154), sweet corn (29), and soybeans (114,119).…”
Section: Host Range Feeding Behavior and Nutritional Ecologymentioning
confidence: 99%
“…Four replicated sets of four experimental 3 × 3 m plots were established within two rows (1.5 m row spacing) of agricultural plastic mulch with four 0.75 × 1 m sub-plots planted with one of four known host plant species (Figure 1). Three host plants bell peppers, sweet corn, and soybean were chosen to represent known, highly attractive host plants with varying phenological stages and the fourth host, Swiss chard, was chosen as a nonfruiting host (Nielsen et al, 2011;Zobel et al, 2016). In 2013, the 3 × 3 m plots were separated by 3 m of bare ground and unplanted plastic mulch which was expanded in 2014 to 5 m. Within the center of each plot, a hole was dug so that a 3.78 l round plastic pot could be placed flush with the surface of the ground, allowing for the deployment of a potted sentinel host plant within each of the 16 plots.…”
Section: Field Layout and Treatmentsmentioning
confidence: 99%